Computational Fluid Dynamic Using Parallel Loop of Multi-Cores Processor - Jaswar, Jaswar; Afrizal, Efi; Siow, C.L (Applied Mechanics and Materials, 2014)
Computational Fluid Dynamics (CFD) software is often used to study fluid flow and structures motion in fluids. The CFD normally requires large size of arrays and computer memory and then caused long execution time. However, Innovation of computer hardware such as multi-cores processor provides an alternative solution to improve this programming performance. This paper discussed loop parallelize multi-cores processor for optimization of sequential looping CFD code. This loop parallelize CFD was achieved by applying multi-tasking or multi-threading code into the original CFD code which was developed by one of the authors. The CFD code was developed based on Reynolds Average Navier-Stokes (RANS) method. The new CFD code program was developed using Microsoft Visual Basic (VB) programming language. In the early stage, the whole CFD code was constructed in a sequential flow before it is modified to parallel flow by using VBs multi-threading library. In the comparison, fluid flow around the hull of round-shaped FPSO was selected to compare the performance of both the programming codes. Besides, executed results of this self-developed code such as pressure distribution around the hull were also presented in this paper.